Cognitive Performance of the Elderly People in an Urban Area of Bangladesh: A Sociodemographic Study - Oishee, Irtifa Aziz; Tanira, Shaorin; Shahrin, Tunazzina; Tamal, Syed Shafiq; Jahan, Nusrat; Moni, Monira Akhter (Community Based Medical Journal, 2024)
A cross-sectional, analytical study was conducted to see the sociodemographic characteristics of elderly people and their association with cognitive performance in an urban setting in Dhaka, Bangladesh, between January and December of 2016. A convenient sampling technique was adopted. A total of 189 elderly people (118 male and 71 female) were included in the study. A semi structured questionnaire was first developed in English and then translated into Bangla. The questionnaire contains questions related to sociodemographic characteristics of the respondents and their cognitive functions, as determined by using Mini Mental state Examination (MMSE). Sociodemographic data were analyzed with descriptive statistics. Pearson correlation test was applied to determine the relationship between quantitative variables, while Chi-square test was done to assess association of qualitative data. The age of the respondents ranged from 60 to 90 years. The mean age was 67.8±6.26 years. Higher proportion of male (37.3%) and female respondents (36.6%) were in 60-64 age group, while the lower proportion was in ≥75 years age group (male 12.7% and female 14.1%). Most of the male respondents were graduate and above education group (64.4%), while most female respondents belonged to SSC and below and informal education group (50.7%) group. The rest of them fell into HSC education group: 11% and 32.4% respectively. Most of the elderlies (57.67%) belonged to the extended family and the rest lived in the nuclear family (42.33%). Among the male respondents, 76.3% were retired. Rest of the respondents was service holder (9.3%), businessman (12.7%) and teacher (1.7%). Female respondents were mostly housewives (97.2%) and two were teachers (2.8%). Among 189 respondents, 35.4% had normal cognitive function. Half of the respondents (52.4%) had mild cognitive impairment and the rest had moderate cognitive impairment (12.2%). None had severe cognitive impairment. Significant relationships of the cognitive performance were observed with age, sex, marital status, educational status, and type of family they lived in. However, no significant association was found between occupation and cognitive performance. CBMJ 2024 January: vol. 13 no. 01 P: 9-16